Rumphius’ Naturkunde: Zirkulation in kolonialen Wissensräumen (Harrassowitz Verlag, 2020)
The naturalist Georg Everhard Rumphius (1627-1702) was a merchant in the Dutch East India Company. His texts D'Amboinsche Rariteitkamer (1705) and Het Amboinsche Kruid-boek (1741-1755) have so far been archived in terms of scientific history as a contribution to botanical and zoological taxonomy and in terms of literary history canonized as part of Dutch-language colonial literature. The interdisciplinary study analyzes the production of knowledge based on the natural history texts by Rumphius. Based on the dynamics of their creation on the Moluccan island of Ambon, the texts and illustrations are questioned about the possibility of new knowledge spaces between today's Indonesia and Northwest Europe, whereby the production and reception of natural history knowledge is understood as circulation in the contact between Asian and European actors. The authors analyze material and medium alternately from historical and literary perspectives. While the investigation of the materiality is devoted to samples, collections and books and the associated practices of collecting, organizing and publishing, the literary text analyzes locate Rumphius' texts in terms of genre poetry and focus on their polyphony and narrativity. In this way, the book represents a valuable contribution to the history of knowledge of European colonial enterprises of the 17th and 18th centuries.